(3ESeGY GdUe aj EKHGJ GdTQa ef bHd GdCes - (3CHh YHO Gddg eMeO Hf YHO GdQMef GHf CHh RjO GdeQGcTj, GdVQjQ,J (B807 (3g` s
(3ChdgG (B:s
(3hHYO abO SCdfi ef dGJSYfj eNGdaJg , aCLHJ dPdc , dbhdg JYGdi(B:" (3hEPG CNP Gddg ejKGb GdPjf ChJhG GdcJGH dJHjfg GdfGS s
(3BNQgG (B:s
(3hjYdj HfGAg , hjQVjg ai GeJg GfJgi s
(3Vef eLehY , JQJjHgG (B: (3BNQ GdeLehYIs
(3GfXQ GjVG GdbSe GdChd HQbe(B36 (3JGQjNs
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B193s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B247 ; (3HQhcdeGf (B- (3GdLRA (B2 - (3U (B347 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B30 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs